2015
DOI: 10.1093/nar/gkv328
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of Dicer: the complexity of the mechanisms regulating Dicer gene expression and enzyme activities

Abstract: There is increasing evidence indicating that the production of small regulatory RNAs is not the only process in which ribonuclease Dicer can participate. For example, it has been demonstrated that this enzyme is also involved in chromatin structure remodelling, inflammation and apoptotic DNA degradation. Moreover, it has become increasingly clear that cellular transcript and protein levels of Dicer must be strictly controlled because even small changes in their accumulation can initiate various pathological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 195 publications
(273 reference statements)
0
64
0
7
Order By: Relevance
“…One post-transcriptional mechanism by which p70 S6K could possibly downregulate the levels of mature miR-145 is by suppressing the maturation of miR-145. Previous reports have demonstrated that Dicer serves as a major regulator of the miRNA biogenesis machinery [26]. Knocking down Dicer clearly abolished the p70 S6K siRNA-mediated suppression of MCS formation (Figure 6B), suggesting a novel link between p70 S6K and Dicer in MCS formation and warrants a closer examination into the mechanism through which p70 S6K regulates Dicer.…”
Section: Resultsmentioning
confidence: 59%
“…One post-transcriptional mechanism by which p70 S6K could possibly downregulate the levels of mature miR-145 is by suppressing the maturation of miR-145. Previous reports have demonstrated that Dicer serves as a major regulator of the miRNA biogenesis machinery [26]. Knocking down Dicer clearly abolished the p70 S6K siRNA-mediated suppression of MCS formation (Figure 6B), suggesting a novel link between p70 S6K and Dicer in MCS formation and warrants a closer examination into the mechanism through which p70 S6K regulates Dicer.…”
Section: Resultsmentioning
confidence: 59%
“…Therefore, the saturation of exportin-5 with pre-miRNAs and some tRNAs decreases the export of Dicer mRNA to the cytoplasm and as a consequence reduces further Dicer gene expression [29]. In addition, recent studies reported that the tumor suppressors p53, p63 and p73 contributed in regulation of Dicer at transcriptional level [30]. Considering all these data, the expression of Dicer regulated with various molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Dicer can have various binding partners that influence its activity levels, including TRBP and PACT. 18 It will be important to determine how HDACi treatment affects their ability to interact with Dicer, their regulation of Dicer activity, and their expression levels. Furthermore, we showed that Argonaute-2 was enhanced by Panobinostat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dicer, an RNase III endoribonuclease, is responsible for cleaving the pre-miR into a mature miR duplex in the cytoplasm and is indispensable to most miR biogenesis. 18 Upon completion of miR maturation, the mature miR duplex is unwound and the guide strand is loaded onto the RNA-induced silencing complex (RISC). 17 The RISC is responsible for bringing the miR to its target mRNAs, where it binds to the 3 0 UTR and leads to translation inhibition or degradation of the target mRNA.…”
Section: Introductionmentioning
confidence: 99%